Acute Epigallocatechin 3 Gallate (EGCG) Supplementation Delays Gastric Emptying in Healthy Women: A Randomized, Double-Blind, Placebo-Controlled Crossover Study - Fernandes, Renata C.; Araujo, Vanessa A.; Giglio, Bruna M.; Marini, Ana Clara B.; Mota, Joao F.; Teixeira, Kim-Ir-Sen S.; Monteiro, Paula A. [UNESP]; Lira, Fabio S. [UNESP]; Pimentel, Gustavo D. (Mdpi, 2018)
Background: Epigallocatechin 3 Gallate (EGCG) appears to act in appetite control through hormonal modulation. However, there is a lack of elucidation of EGCG's action mechanisms, especially in humans. The aim of this study was to evaluate the effects of acute EGCG supplementation on gastric emptying and its relation to blood hormones, glucose and appetite perceptions in healthy women. Methods: 22 healthy adult women were included in a randomized, double-blind, placebo-controlled crossover study. On two separate occasions, 1 week apart from each other, we offered 800 mg of corn starch (placebo) or 752 mg of EGCG. Appetite was assessed through gastric emptying; perceptions of hunger, desire to eat and satiation; and plasma insulin, adiponectin, leptin and glucose concentrations. The evaluations were carried out in fasting, 30, 90 and 150 min after supplementation. Results: EGCG supplementation induced higher relative gastric volume at 30 and 90 min. Satiation at 90 min was higher in the EGCG group. Adiponectin concentrations at 150 min were higher with EGCG, but no difference was found for glucose, insulin and leptin concentrations. Conclusions: Acute EGCG supplementation is able to delay gastric emptying in healthy women to a small, but statistically significant extent. This study was registered at the Brazilian Registry of Clinical Trials (ReBEC) as RBR-9svwrv.
Keywords: Camellia sinensis; EGCG; catechin; gastric emptying; satiety response; satiation